Use of Distribution Function in Estimation of Mean of Some Demographic Duration Variables - Yadava, R. C.; Tiwari, Abhay Kumar; Patel, Vaishali; Singh, Pappu Kumar (Journal of Reliability and Statistical Studies, 2025)
Life testing, Survival analysis and Reliability theory, although highly inter-related, are fascinating areas of statistical research. Here, the random variable, normally known as ‘Life Time’ of the equipment, is a duration variable which takes only non-negative values. Some examples have been given in the study to demonstrate the similarities between life testing and some demographic phenomena. Several procedures exist for analysing the nature of demographic duration variables such as life expectancy at birth, age at marriage, postpartum amenorrhea, breastfeeding etc. The objective of the present paper provides the procedure that how the mean of some demographic duration variables (life expectancy at birth, age at marriage, postpartum amenorrhea, breastfeeding etc.) can easily be obtained using distribution function? This method is straightforward because the required data to compute the mean is easily obtained without any misreporting, recall lapses or digit preferences of durational variables. For this study, we have considered data from UN population division (Economic and Social Affairs) and national family health survey (NFHS). Results indicate that the estimated expectancy of life at birth, mean age at marriage, average duration of postpartum amenorrhea and breastfeeding using mentioned procedure are close to observed value.